The Influence of the Auditory Intellectual Repetition (AIR) Learning Model on Science Learning Outcomes in Islamic Elementary School - AR, Sari Meutia; Adriyani, Zuanita (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research was conducted at MI Baitul Huda Semarang. This research focuses on fifth-grade students for the 2022/2023 academic year. This study aims to determine the effect of the Auditory Intellectually Repetition (AIR) learning model on science learning outcomes in the theme material of the eight water cycles. This research is motivated by a lack of activity, enthusiasm, and low scores in science learning outcomes. This research approach is to use a quantitative approach. This study used a purposive sampling technique with a one-group pretest-posttest design model, namely an experiment conducted in one group only without any comparison group. The population used in this study was class V MI Baitul Huda, a total of 61 students, and focused on class VB as many as 30 students as a sample. The data collection method used is the test method with multiple choice objective tests. This study uses two sources of data, namely primary and secondary. The primary data source is student class V MI Baitul Huda Semarang which is the subject, and secondary data is documentation, teacher books, student books, and other supporting books. Data were analyzed using the t-test, which used the paired sample t-test. It was found that the results of the t-test were 0.000 <0.05, which means that the hypothesis is accepted, meaning that there are differences in science learning outcomes in class VB students before using the AIR model and after using the AIR model. Based on the test results of the coefficient of determination, the coefficient of determination (R Square) is 30.0%, which means that the AIR learning model influences science learning outcomes. Based on the results of the research that has been done, it is concluded that the AIR learning model influences science learning outcomes in class V MI Baitul Huda in the 2022/2023 academic year.